Teak Log Coffins in Northwest Thailand: Dated by Dendrochronology and 14Cwiggle Matching - Nathsuda Pumijumnong; Sineenart Wannasri (Applied Environmental Research, 2015)
Log coffins have been discovered in caves and rockshelters in the Pang Ma Pha district, Mae Hong Son province, Northwestern Thailand. Most are made of teak wood. Many researchers have used the 14C method to determine their age. However, 14C cannot provide as precise a calendar age as dendrochronology. In this paper, we therefore applied dendrochronology analysis to a number of teak log coffins at the Ban Rai Rockshelter to establish a floating chronology and to cross-date the coffins relative to each other. Then, wiggle matching was used for one log coffin to derive an approximate but absolute calendar age. The findings indicated that cutting of this teak tree occurred around AD 265. The analyses also revealed a close association between coffins of the same head style.